Pengaruh Kompensasi dan Karakteristik Pekerjaan Terhadap Kepuasan Kerja Karyawan Unit Produksi Pada PT. Adi Karya Makassar - Ansar Taufik (Jurnal Online Manajemen ELPEI, 2021)
This research was conducted to find out the influence of compensation variables and job characteristics on the work satisfaction of Production Unit employees at PT. Adi Karya This research is causality research and the method used in this research is survey. The number of samples is 93 respondents and the data collected is carried out by filling out some questionaires. There are two groups of variables in this research. Those are independent variables which are compensation and job characteristics, and the other is dependent variable which is work satisfaction of Production Unit employees at PT. Adi Karya Multiple linear regression is used to analyze the influence of variables on compensation and job characteristics on the work satisfaction. According to the results of regression analysis, find that simultaneously variables of compensation and job characteristics have significant effects on work satisfaction of production Unit employee at PT.. Adi Karya Partially, the variable of job characteristic which is autonomy of job (X3) has the most dominant effect on work satisfaction of production unit employees at PT. Adi Karya